The academic and non-academic factors related to students' subject failing and attrition at the philosophy departament of the school of arts and sciences of the University of El Salvador, semester I-2000 - Menjívar Méndez, Roxana Guadalupe; Merlín Zarzol, Zenaida Jacqueline; Blandón de Castro, Norma Cecilia (San Salvador : Universidad de El Salvador, 2002)
The present report has been prepared by Seminar I students to find out the academic and non-academic factors related to student subject failing and attrition in the Philosophy Department at the School of Arts and Sciences of the University of El Salvador in Semester I-2000. This document includes the antecedents and the statement of the problem in which the research project was based. A list of research questions and objectives that guided the investigation and the theoretical framework which contains the theoretical aspects related to the topic, are also presented here, based on the consulted bibliography. The hypotheses and methodology used to get the sample section of the Philosophy Department that describes not only the population and sample of the study, but also the statistical procedure to calculate that sample and the instrument that was used to collect the data is included. In addition to this the analysis of the data with their own graphs were added. And finally the list of the consulted references and the annexes are presented.
Incluye anexos
Tesis (Licenciatura en Idioma Inglés) -- Universidad de El Salvador, San Salvador, 2002
Incluye bibliografía
Keywords: Rendimiento académico; Deserción universitaria